2013
DOI: 10.4172/2157-7412.1000120
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Mood Disorders

Abstract: Background Mood disorders are expressed in many heterogeneous forms, varying from anxiety to severe major clinical depression. The disorders are expressed in individual variety through manifestations governed by co-morbidities, symptom frequency, severity, and duration, and the effects of genes on phenotypes. The underlying etiologies of mood disorders consist of complex interactive operations of genetic and environmental factors. The notion of endophenotypes, which encompasses the markers of several underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 223 publications
(213 reference statements)
2
5
0
Order By: Relevance
“…This result also replicates findings among Swedish pupils where self-fulfilling, high and low affective participants showed higher level of life satisfaction compared with self-destructives (e.g., Garcia & Archer, 2012). As suggested by Lindahl & Archer (2013; see also Archer & Kostrzewa, 2013; Archer et al, 2013), positive affect might serve as an anti-depressive factor and, as suggested here, also as a protective factor for happiness and life satisfaction.…”
Section: Discussionsupporting
confidence: 60%
“…This result also replicates findings among Swedish pupils where self-fulfilling, high and low affective participants showed higher level of life satisfaction compared with self-destructives (e.g., Garcia & Archer, 2012). As suggested by Lindahl & Archer (2013; see also Archer & Kostrzewa, 2013; Archer et al, 2013), positive affect might serve as an anti-depressive factor and, as suggested here, also as a protective factor for happiness and life satisfaction.…”
Section: Discussionsupporting
confidence: 60%
“…This result also replicates findings among Swedish pupils where self-fulfilling, high and low affective participants showed higher level of life satisfaction compared with self-destructives (e.g., . As suggested by Lindahl and Archer (2013;see also Archer & Kostrzewa, 2013;Archer, Oscar-Berman, Blum & Gold, 2013), positive affect might serve as an anti-depressive factor and, as suggested here, also as protective factor for happiness and life satisfaction.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, these adaptations occur at the cellular, molecular, or epigenetic level and are associated with synaptic plasticity and modified gene expression. These effects on gene expression can occur via factors influencing translation (epigenetics) and transcription (non-coding micro RNAs) of the DNA or even RNA itself [ 68 – 70 ].…”
Section: Addiction Epigeneticsmentioning
confidence: 99%